Answer:
x³ - 12 = (x - ∛12)(x² + x∛12 + 12²/³)
Explanation:
Question is incomplete (options are missing);
However, I'll factorize the polynomial using identity
Given
x³ - 12
This can be factorized using the following identity
a³ - b³ = (a - b)(a² + ab + b²)
By comparison,
a³ = x³ and b³ = 12
a = x and b = ∛12
Replace a with x and b with ∛12 in the above equation
a³ - b³ = (a - b)(a² + ab + b²) becomes
x³ - 12 = (x - ∛12)(x² + x∛12 + ∛12²)
x³ - 12 = (x - ∛12)(x² + x∛12 + 12²/³)
This is as far as it can be factorized
So, the factorization of x³ - 12 using identity is (x - ∛12)(x² + x∛12 + 12²/³)